Effect of Different Plant Growth Regulators on Micropropagation of Some Pitaya Varieties : Micropropagation of Some Pitaya Varietie - Taner Bozkurt; Sezen Inan; Ijlal Dundar; Selda Kozak (Journal of Tropical Life Science, 2022)
Pitaya belongs to the family Cactaceae and the genus Hylocereus. It is essential todevelop tissue culture protocols according to the appropriate variety to spread pitayacommercial production and ensure healthy sapling production. This study aimed todetermine the best plant growth regulators (PGRs) in the micropropagation process,and their effects on different pitaya cultivars were evaluated. Shoots of different pitayacultivars were cultured in Murashige and Skoog (MS) basal medium supplementedwith Indole-3-butyric (IBA), 6-benzyl amino purine (BAP), and gibberellic acid(GA3). The highest micropropagation coefficient was determined in Physical Graffitivariety cultured in MS medium supplemented with 2 mg/L BAP. The general evaluation based on the variety determined that the best micropropagation was in the RoyalRed variety. In in vitro rooting studies, the best rooting variety was Royal Red(54.47%), followed by Siam Red (50.33%), Physical Graffiti (47.75%), and SeoulKitchen (44.82%). It was determined that the Royal Red variety is grown in R2 (MSmedium supplemented with 1 mg/l IBA) medium gave the best results in all criteriaof shoot length (4.28 cm), root length (6.45 cm), and root formation on the face(74.48%). It was envisioned that these differences between the micropropagation,growth, and rooting of the cultivars used in the studies resulted from the cultivar characteristics.Keywords: Pitaya, In vitro, Micropropagation, Royal Red, Seoul Kitchen, Siam Red,Physical Graffiti